Selecting forage sorghum cultivars for silage - White, J.; Bolsen, K.; Kirch, B.; Pfaff, L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Eighty forage sorghum cultivars were compared in 1986 for agronomic and silage quality traits. Silage yield ranged from 5.3 to 10.0 tons (t) of dry matter (DM) per acre (mean, 7.4 t); grain yield, from 13 to 113 bushels (bu) per acre (mean, 66 bu). Percent lodging was extremely high, with a mean of 51% and only one cultivar free of lodging. Pre-ensiled DM content ranged from 22.2 to 35.4% (mean, 27.4%) and plant height from 85 to 180 inches (mean, 121 inches). Silage quality results showed that in vitro DM digestibility ranged from 44.6 to 62.1% (mean, 53%); crude protein from 4.5 to 8.2% (mean, 6.8%); neutral detergent fiber from 48.3 to 71.9% (mean, 58.4%); and acid detergent fiber from 27.1 to 49.8% (mean, 35.7%). From the 80 cultivars in 1986, 60 were selected for the 1987 trial. When compared to 1986, the 1987 means showed slightly lower silage (7.0 t) and grain (63 bu) yields and much shorter plants (93 inches). Lodging scores were dramatically lower in 1987 (10%), and DM content was higher (29.1%). The year to year effect influenced all of the agronomic traits measured. The 1986 growing season favored the early maturing forage sorghums, whereas 1987 favored the late maturing cultivars.
Keywords: Beef; Forage sorghum cultivars; Silage; Grain yield